High-power Microwaves Against Locust Invasion - Zapevalov, Vladimir (Current Physics, 2024)
BackgroundThere are a lot of phytophagous and harmful animals in agriculture and forestry in the entire world. The ultimate goal in locust control is the use of preventive and proactive methods that disrupt the environment to the least possible extent. This would make agricultural production easier and more secure in the many regions where growing crops is of vital importance.MethodsThe possibility of using high-power microwave systems to combat harmful animal pests in agriculture and forestry is discussed. The proposed method is compared favorably with respect to the environment.ResultsThe obtained results of the study demonstrated the possibility of using modern sources of high-power microwave radiation to solve the problem of insect invasion.ConclusionIt should be noted that the use of powerful microwaves is a promising means of controlling locusts and other pests. Mobile international forces equipped with modern microwave apparatus can solve the problem of combating locusts and other pests on a global scale without harming the environment. Microwave systems can also be used against other phytophagous pests of agriculture and forestry.
Keywords: microwaves